Retinal oximetry in normal and amblyopic children: a pilot study. Issue 7 (7th March 2019) - Mohan, Ashwin; Kemmanu, Vasudha; Baliga, Swathi; Patil, Minal; Madhavrao, Bhanumathi; Webers, Carroll A.B.; Yadav, Naresh Kumar; Shetty, Rohit; Berendschot, Tos T.J.M.
Abstract: Purpose: To study the retinal vascular oxygen saturation in amblyopic eyes and compare them to unaffected fellow eyes and eyes of normal subjects. Methods: A total of 32 amblyopic, 24 normal and 13 fellow eyes of patients below age of 18 were enrolled in this prospective observation study. Retinal oximetry was performed using the Oxymap T1 retinal oximeter. Retinal vascular oxygen saturations and diameters were compared between amblyopic eyes, normal eyes and unaffected fellow eyes. Results: The average age was 8.6 years in the amblyopia group (M:F 16:16) and 10.9 years in the normal group (M:F 7:5; p = 0.024). Median corrected distance visual acuity in the amblyopia group was 20/50; it was 20/20 in the other groups (p < 0.001). The average arteriolar and venous saturation in the amblyopia, normal and fellow group was 84.5% (95% CI: 82.6–86.4), 83.2% (95% CI: 80.7–85.6) and 80.8% (95% CI: 78.6–82.9) and 51.9% (95% CI: 50.4–53.4), 50.8% (95% CI: 48.2–53.4) and 49.3% (95% CI: 45.7–52.9). There was no statistically significant difference between the saturation values of the amblyopia group and the controls, however, significantly higher values were found in the amblyopia group compared to the fellow group for arteriolar and venous saturations (p = 0.013; p = 0.005). Arteriolar and venous diameters showed no significant difference between groups. Conclusion: Amblyopic eyes showed higher mean oxygen saturations than the fellow eyes. This observation could be due to altered neuronal activity or could be due to a measurement artefact due to alterations in retinal reflectivity.